Pengaruh Kompres Jahe Terhadap Keluhan Nyeri Sendi - Mujahidin, Mujahidin (JURNAL KESEHATAN TERAPAN, 2023)
Joint pain is one of the most common health complaints in the community. This complaint is often found in individuals with an age range of 50 to 70 years, this complaint is believed to have a fairly close relationship with the aging process. The complaints submitted are quite typical, namely in the form of pain that feels specific to the joint area. There are two methods that are usually used to treat complaints of joint pain, namely pharmacology and non-pharmacology. Non-pharmacological pain management can be done using distraction techniques and relaxation techniques. The use of ginger as an alternative to pain management has begun to be widely used in certain cases, such as in cases of gout pain, gout arthritis pain, osteoarthritis pain and joint pain where the cause is still unknown. The purpose of this study was to determine the effect of ginger compresses on complaints of joint pain. The method in this study was one group pre test post test design, the research sample was 30 residents who experienced complaints of joint pain, data analysis used the Wilcoxone test. This research was conducted in November-December 2022 in Lubuk Ketepeng Village, Jejawi District, Ogan Komering Ilir Regency. The results obtained p value 0.005. It was concluded that there was a significant effect of ginger compresses weighing 1 gram and carried out for 2 hours on complaints of joint pain.